Mathematics (T) calculus - Wong, Pek Mei; Lye, Min Soon (Ace Ahead STPM Text, 2019)
This comprehensive coursebook is written based on the latest STPM Mathematcis (T) syllabus. It serves to fully prepare students sitting for the Mathematics (T) Paper 2 of the latest STPM assessment system. The coursebook with illustrative diagrams, provide an in-depth understanding of the important principles and concepts in mathematics.